(untitled) (Bangladesh Journal of Zoology, 2024)
Predatory potential of Zebrafish, Danio rerio (Cypriniformes: Cyprinidae) and Guppy, Poecilia reticulata (Cyprinodontiformes: Poeciliidae) were evaluated to control Aedes mosquito larvae and thereby manage dengue epidemics in a sustainable, and eco-friendly manner. Under laboratory conditions, size-matched fish of each species were introduced into separate plastic containers containing 2 liters of tap water and 100 third instar larvae of Aedes. In addition, different prey combinations were used to assess the comparative predation potential of the fishes. Mosquito prey preferences were assessed using Manly’s preference index. Over 24-hours of laboratory conditions, a significant difference (p<0.05) between the predatory efficiency of the studied fish species was reported where the predatory efficiency of D. rerio was higher than that of Po. reticulata. D. rerio showed significantly (p<0.05) higher predation efficiency and prey preference for 2nd instar larvae and pupae of Aedes than Po. reticulata on the presence of alternative prey. Based on predation efficiency and prey preference, this study suggests that indigenous Danio rerio can be evaluated as an alternative species to exotic Poecilia reticulata in biological control for more eco-friendly, cost-effective sustainable management of Aedes mosquitoes. Bangladesh J. Zool. 51(3): 315-327, 2023